Changing the narrative: Resilience of women in STEM in sub-Saharan Africa and institutional innovations to advance equity - Monica Fisher; Violet Nyabaro; Ruth Mendum; Sujata Ganguly; Moses Osiru (PLoS ONE, 2026)
Gender disparities in science, technology, engineering, and mathematics (STEM) remain pronounced in many African countries, particularly at the postgraduate level. This study explores the experiences of African women in STEM postgraduate education by integrating data from an online survey of 163 female PhD alumni from 40 African universities in 17 countries and seven focus group discussions (FGDs) with 39 current postgraduate students across three countries. Through a mixed-methods approach, we examine both the challenges women face and the factors that enable their persistence and success. Over 60% of respondents reported financial stress during their PhD, and more than half felt unprepared at the time of program entry. Yet 95% expressed confidence in their ability to succeed, reflecting strong self-efficacy despite structural barriers. In the FGDs, women highlighted the burden of caregiving responsibilities, lack of role models, and cultural norms that pressure them to prioritize family over academic careers. Contrary to common assumptions, most FGD participants preferred male supervisors, citing competitiveness or lack of support from some senior women. Despite these obstacles, participants demonstrated high levels of resilience, often driven by a passion for science and strong family support. Our findings highlight the need for family-friendly policies, structured and tailored mentoring, and flexible, gender-responsive institutional reforms to ensure more inclusive and equitable STEM postgraduate environments in Africa.